2016
DOI: 10.1016/j.jgr.2015.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gintonin on the proliferation, migration, and tube formation of human umbilical-vein endothelial cells: involvement of lysophosphatidic-acid receptors and vascular-endothelial-growth-factor signaling

Abstract: BackgroundGinseng extracts are known to have angiogenic effects. However, to date, only limited information is available on the molecular mechanism underlying the angiogenic effects and the main components of ginseng that exert these effects. Human umbilical-vein endothelial cells (HUVECs) are used as an in vitro model for screening therapeutic agents that promote angiogenesis and wound healing. We recently isolated gintonin, a novel ginseng-derived lysophosphatidic acid (LPA) receptor ligand, from ginseng. LP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 42 publications
(73 reference statements)
0
33
0
Order By: Relevance
“…In the present study, the migration and tube formation of HUVECs increased significantly following the treatment with 10 and 100 µg/ml CCL. The increased movement of endothelial cells during angiogenesis was previously found to be closely linked to the formation of new blood vessels in wounds (19,20). Ashcroft et al (21) reported accelerated wound healing through a reduction of inflammation, and pro-inflammatory cytokines were shown to play a crucial role during this healing response.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the present study, the migration and tube formation of HUVECs increased significantly following the treatment with 10 and 100 µg/ml CCL. The increased movement of endothelial cells during angiogenesis was previously found to be closely linked to the formation of new blood vessels in wounds (19,20). Ashcroft et al (21) reported accelerated wound healing through a reduction of inflammation, and pro-inflammatory cytokines were shown to play a crucial role during this healing response.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, VEGFR2 has been shown to play a major role in VEGF-dependent angiogenesis (24). Additionally, IL-6 acts on a variety of organs and cell types and promotes cell growth, and its expression has been reported during wound healing (15,19,20). Furthermore, TNF-α has been implicated as an indirect angiogenic factor, and various cytokines including IL-1b have been shown to be associated with VEGF-dependent angiogenesis (10,17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Its main functional ingredients are LPAs. We have also shown that gintonin LPAs function as an LPA receptor-ligand exhibiting diverse biological effects in vitro and in vivo [4][5][6][7][8][9]. In a subsequent study, we showed that gintonin contains other bioactive lipids besides LPAs, listed in order of prevalence: linoleic acid > phosphatidic acids > LPAs > LPIs [12].…”
Section: Discussionmentioning
confidence: 82%
“…Viability of INS-1 cells was determined by a sodium 2,3,-bis(2-methoxy-4-nitro-5-sulfophenyl)-5-[(phenylamino)-carbonyl]-2H-tetrazolium inner salt) (XTT)-based assay, as previously described, with some modifications [4,8]. Briefly, cells were seeded at 3 × 10 3 cells per well into 96-well plates.…”
Section: Cell Viabilitymentioning
confidence: 99%
See 1 more Smart Citation